Use of the mouse ear vesicant model to evaluate the effectiveness of ebselen as a countermeasure to the nitrogen mustard mechlorethamine. Issue 12 (17th December 2013) - Lulla, Anju; Reznik, Sandra; Trombetta, Louis; Billack, Blase
ABSTRACT Previous studies in this and other laboratories have demonstrated that ebselen (EB‐1), an organoselenium compound, spares cells from mechlorethamine (HN2) toxicity in vitro. In the present study, the hypothesis that EB‐1 will reduce dermal toxicity of HN2 in vivo is put forward and found to have merit. Using the mouse ear vesicant model (MEVM), HN2, applied topically, showed a dose‐dependent effect upon ear swelling and thickness 24 h after treatment; whereas tissue injury consistent with vesication was observed at the higher test doses of HN2 (≥ 0.250 µmol per ear). To examine HN2 countermeasure activity using the MEVM, either hydrocortisone (HC), as a positive control, or EB‐1, the test countermeasure, was administered as three topical treatments 15 min, 4 and 8 h after HN2 exposure. Using this approach, both HC and EB‐1 were found to reduce tissue swelling associated with HN2 toxicity 24 h after exposure to the vesicant. Taken together, these data demonstrate for the first time the effectiveness of EB‐1 as a vesicant countermeasure in a relevant in vivo model. Copyright © 2013 John Wiley & Sons, Ltd.